Response Surface Modeling of Remifentanil–Propofol Interaction on Cardiorespiratory Control and Bispectral Index - Nieuwenhuijs, Diederik J.F.; Olofsen, Erik; Romberg, Raymonda R.; Sarton, Elise; Ward, Denham; Engbers, Frank; Vuyk, Jaap; Mooren, Rene; Teppema, Luc J; Dahan, Albert (Anesthesiology (Philadelphia), 2003)
Since propofol and remifentanil are frequently combined for monitored anesthesia care, we examined the influence of the separate and combined administration of these agents on cardiorespiratory control and bispectral index in humans. The effect of steady-state concentrations of remifentanil and propofol was assessed in 22 healthy male volunteer subjects. For each subject, measurements were obtained from experiments using remifentanil alone, propofol alone, and remifentanil plus propofol (measured arterial blood concentration range: propofol studies, 0-2.6 microg/ml; remifentanil studies, 0-2.0 ng/ml). Respiratory experiments consisted of ventilatory responses to three to eight increases in end-tidal Pco2 (Petco2). Invasive blood pressure, heart rate, and bispectral index were monitored concurrently. The nature of interaction was assessed by response surface modeling using a population approach with NONMEM. Values are population estimate plus or minus standard error. A total of 94 responses were obtained at various drug combinations. When given separately, remifentanil and propofol depressed cardiorespiratory variables in a dose-dependent fashion (resting V(i) : 12.6 +/- 3.3% and 27.7 +/- 3.5% depression at 1 microg/ml propofol and 1 ng/ml remifentanil, respectively; V(i) at fixed Petco of 55 mmHg: 44.3 +/- 3.9% and 57.7 +/- 3.5% depression at 1 microg/ml propofol and 1 ng/ml remifentanil, respectively; blood pressure: 9.9 +/- 1.8% and 3.7 +/- 1.1% depression at 1 microg/ml propofol and 1 ng/ml remifentanil, respectively). When given in combination, their effect on respiration was synergistic (greatest synergy observed for resting V(i)). The effects of both drugs on heart rate and blood pressure were modest, with additive interactions when combined. Over the dose range studied, remifentanil had no effect on bispectral index even when combined with propofol (inert interaction). These data show dose-dependent effects on respiration at relatively low concentrations of propofol and remifentanil. When combined, their effect on respiration is strikingly synergistic, resulting in severe respiratory depression.